Tackling disability discrimination and disability hate crime : a multidisciplinary guide - Shah, Robina; Giannasi, Paul (Jessica Kingsley Publishers, 2015)
Placing the experiences of victims at its heart, this book provides an authoritative overview of disability hate crime - explaining what it is, how it happens, its legal status, the impact on victims and how individuals and agencies should respond. The guide outlines innovative projects developed to address the problem, and provides tailored guidance for professionals spanning education, health and social care, and criminal justice. It also offers recommendations for effective multi-agency working. After highlighting the crimes committed against disabled people and society's failure to protect them, the book concludes with a powerful argument for cross-government action to improve professional practice and eliminate disability-motivated hate crime.